Melanotic neuroectodermal tumor of infancy: a case report - Çetik, Fikret; Tuncer, İlhan; Kıroğlu, Fikret; Soylu, Levent; Doran, Figen (The Turkish Journal of Pediatrics, 1988)
A typical case of melanotic neuroectodermal tumor of infancy, located on the maxilla of a six-month-old boy is presented and the literature is discussed.
Keywords: melanotic neuroectodermal tumor; neural crest